DO PROFITABILITY, LEVERAGE, AND DIVIDEND POLICY INFLUENCE FIRM VALUE? EVIDENCE FROM INDONESIA’S ENERGY INDUSTRY - Iswandari, Dini; Iswandari, Siti (UIN Sunan Gunung Djati Bandung, 2026)
The purpose of this study is to analyze the overall impact of dividend, leverage, and profitability policies on energy companies listed on the Indonesia Stock Exchange during 2019-2023. Secondary data were obtained from financial statements, and 17 companies were selected using directional sampling over a five-year observation period. The analysis employed Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 to provide methodological insights. By focusing on the energy sector during the pandemic and the recovery period, this study provides a timely context, addressing the gap in prior studies that were primarily focused on the industrial sector and banking and employed conventional regression methods. The findings indicate that profitability and leverage significantly affect firm value, whereas dividend policy does not exhibit a notable impact. An R-squared of 41.8% suggests that the independent variables account for only part of the variation in the company's value, with the remainder attributable to external factors. From a managerial perspective, the findings emphasize the need to prioritize profitability and manage leverage carefully to increase firm value. At the same time, dividend policy should not be treated as a determinant in investor evaluation. To gain broader insight, future studies are recommended to extend the analysis to other industries and increase the sample size.